The difficulty of studying the association between pathway delays and survival in cancer – an example from bladder cancer - Beth Russell; Oskar Hagberg; Christel Häggstrom; Lars Holmberg; Mieke Van Hemelrijck; Fredrik Liedberg (Scandinavian Journal of Urology)
N/A